Health-Related QOL Improved with Tofacitinib in Patients with Psoriasis - Rizzo, Toni (MD Conference Express, 2014)
Moderate to severe plaque psoriasis has both physical and psychological effects, leading to major impairment of health-related quality of life. Tofacitinib, an oral Janus kinase inhibitor, was found to be effective in A Phase 3, Multi Site, Randomized, Double Blind, Placebo Controlled Study of the Efficacy and Safety Comparing CP- 690,550 and Etanercept in Subjects With Moderate to Severe Chronic Plaque Psoriasis [NCT01241591]. The objective of this analysis of the tofacitinib phase 3 trial was to assess the effects of tofacitinib (5 and 10 mg, BID) versus etanercept or placebo on patient-reported outcomes.